Market Analysis & Strategies for the Launch of New Product in the Landscape of Information Security & Assurance by Nexor - Gupta, Debraj (2011)
Nexor has been an active player in the information assurance market for over two decades. They figured a gap in the information security horizon and subsequently undertook a project Carmen to cash in on the opportunity presented by the situation by bridging the gap. As a SME they have spent considerable resources, efforts and time for this. Now the product is ready to be taken to the market but prior to that it is necessary to evaluate the market scenario and possibilities of Carmen‘s success. It was necessary to identify the potential competitors of Carmen, the possible buyers, the Channels for taking Carmen to Market and the various possible pricing strategies to be adopted to make the most of the rare capabilities of this innovation. It was understood that all the products that fall under the category of data loss prevention, intrusion detection, content discovery and a few others have some overlap with certain capabilities of Carmen. Therefore, it was necessary to identify the companies that own these competing products and also the differentiating feature of Carmen. For the target customer segments, the Government sector, the Medical & Healthcare services sector, the telecom sector, the legal services sector and the publishing industry have been analysed to understand what are the possible information security problems faced by them and how Carmen can possibly solve their problems. Thereafter, the various direct and indirect marketing channels have been studied and analysed and it was felt that partnering with system integrators, forging alliances with some companies with access to markets not easily accessible to Carmen and also engaging in directly approaching some of the clients could be the most effective means of taking Carmen to the market. Finally, after evaluating several software pricing models it was felt that using the services pricing and other strategies that translate into steady periodic cash inflow for NEXOR would be the best suited for Carmen pricing, which have been elucidated in further detail in this report.